2020
DOI: 10.1016/j.jcv.2020.104338
|View full text |Cite
|
Sign up to set email alerts
|

Severity of coronavirus respiratory tract infections in adults admitted to acute care in Toronto, Ontario

Abstract: Background: The World Health Organization has highlighted the need for improved surveillance and understanding of the health burden imposed by non-influenza RNA respiratory viruses. Human coronaviruses (CoVs) are a major cause of respiratory and gastrointestinal tract infections with associated morbidity and mortality. Objectives: The objective of our study was to characterize the epidemiology of CoVs in our tertiary care centre, and identify clinical correlates of disease severity. Study design: A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
4
44
1
1
Order By: Relevance
“…These risk factors were largely consistent with those reported previously. [6][7][8][9]14 However, we recognize that there may be additional risk factors not correlated with the CDC risk factors or variables included in the Charlson Comorbidity Index. For example, one in six patients with no CDC risk factors required an ICU stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors were largely consistent with those reported previously. [6][7][8][9]14 However, we recognize that there may be additional risk factors not correlated with the CDC risk factors or variables included in the Charlson Comorbidity Index. For example, one in six patients with no CDC risk factors required an ICU stay.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to describe the presenting characteristics and associated hospital utilization by gender, age, and geography. [6][7][8][9] These initial studies have described COVID-19 hospitalized mortality rates ranging from 5% to 64% based on age and lengths of stay varying from 4-13 days. These studies were limited to narrow geographic areas of New York City, New York; Toronto, Canada; and Wuhan, China.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has highlighted the need to improve epidemiological surveillance and knowledge of the health burden imposed by non-influenza respiratory viruses [15]. HCoVs are generally associated with mild upper respiratory tract infections [16], but severe infections with HCoV-229E, HCoV-NL63, and HCoV-OC43 have been reported [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variation in coronavirus activity has been seen, with most activity occurring in the wintertime, with some exceptions. [45][46][47][48][49][50][51][52][53] A systematic review of seasonal incidence by Li et al 54 recently came to the same conclusion. A Brazilian study in contrast, found that 229E was more common in autumn.…”
Section: General or Adult Population Frequencies And Illnessesmentioning
confidence: 84%
“…Coronaviruses have been associated with exacerbations of chronic lung disease 64,67,74,77,82,92 ; smoking had been identified a possible cofactor for lower respiratory infection. 51,92,96 Some of these exacerbations required hospital admission, and fewer resulted in patient deaths. 67 A study in Italy 42 found OC43 to be more associated with lower respiratory tract infections, but this has not held in most other studies.…”
Section: General or Adult Population Frequencies And Illnessesmentioning
confidence: 99%